Twice I Sought Death - Mann, Marty (Tufts Archival Research Center, 2006)
Founder and Executive Director of the National Committee on Alcoholism, Marty Mann describes her experience with alcoholism, and states her beliefs that suffering is universal but can be used to teach life lessons and that she is uniquely suited to help the suffering of alcoholics.